Penentuan Kandungan Kation dan Anion Mayor dalam Abu Serabut Kelapa Berpotensi Katalis Renewable: Determination of Major Cation and Anion Content in Coconut Fiber Ash Potentially Renewable Catalyst - Darma Santi; Ahmad Muin; Agnes Dyah Novitasari Lestari (JISTECH: Journal of Information Science and Technology, 2014)
Coconut fibers ash contain the cations and anions that can be use as renewable catalyst in certain chemical reaction. Coconut fibers ash that used in this experiments was from Manokwari, Papua Barat. Coconut fibers ash samples was destructed by aqua regia and was analyzed by Atomic Absorption Spectrophotometer (AAS) for determine cations and anions. The another part of sample was decarbonated and extracted with in methanol, then carbonats and bicarbonats were determined using acidimetry method. The AAS analyze results that coconut fibers ash samples in this experiments were contains K (20.140 g/kg); Ca (13.897 g/kg); Mg (4.611 g/kg); Fe (34.502 g/kg); dan Mn (8.957g/kg) cations. The major anions is carbonat (145.54 g/kg) and bicarbonate (50.051g/kg). The kalium content that was high in carbonats makes the aqeous of coconut fibers ash have base properties, it be potentially as renewable catalyst in the certain chemical reaction.